Pengaruh Penerapan Model Pembelajaran Kooperatipe Tipe Think Pair Share (TPS) Terhadap Hasil Belajar Matematika Siswa SMP: Studi Penelitian Ekspermen di SMPN 1 Banyuresmi Garut - Sari, Siska Puspita; Madio, Sukanto Sukandar (Department of Mathematics Education Program IPI Garut, 2013)
This study aims to determine whether the learning outcomes of learning mathematics that uses models of type cooperative think pair share (TPS) is better than that using learning model conventional. From normality test results of initial test data shows that the initial test scores in the experimental class were normally distributed, whereas scores initial tests on the control class distribution are not normal, so proceed with testing at the Mann Whitney test with significance level 0.05. Because the initial tests at the conclusion cannot start capability differences between the experimental class and the control class followed by normalized. based gain test data analysis results can indicate that the initial capacity of the two groups can be concluded there is influence. while the results obtained from the final test at the significant 0,5. because t > t table then Ho rejected. It can be concluded that there is significant mathematical achievement of students who use cooperative learning model think pair share.